2015
DOI: 10.3390/ijerph121215031
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Profiles of Vibrio vulnificus in German Coastal Waters, a Comparison of North Sea and Baltic Sea Isolates

Abstract: Vibrio vulnificus is a halophilic bacterium of coastal environments known for sporadically causing severe foodborne or wound infections. Global warming is expected to lead to a rising occurrence of V. vulnificus and an increasing incidence of human infections in Northern Europe. So far, infections in Germany were exclusively documented for the Baltic Sea coast, while no cases from the North Sea region have been reported. Regional variations in the prevalence of infections may be influenced by differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Nevertheless, owing to the growing importance of Vibrio spp. for tourism and human health during summer months in rapidly warming northern European seas (8,19) we consider this data set worthwhile for publication in order to motivate further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, owing to the growing importance of Vibrio spp. for tourism and human health during summer months in rapidly warming northern European seas (8,19) we consider this data set worthwhile for publication in order to motivate further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio vulnificus enters the body via the consumption of seafood or through an open wound exposed to seawater, contaminated with the bacteria. Due to its high proliferation, wound infections may quickly progress to necrotizing fasciitis and septicemia (14). The investigation was done to gain public awareness of bacteria existence in the area under study.…”
Section: Discussionmentioning
confidence: 99%
“…This warming, combined with natural and anthropogenic eutrophication, increased microbial activity, and increased thermal stratification will likely exacerbate chronic and seasonal hypoxic events. Although hypoxia will increase globally via various mechanisms related to climate change [ Barros et al , ; Rabalais et al , , ], these two areas are interesting in terms of Vibrio infection rates, both historically and continuously from the Gulf of Mexico and newly emerging infections in the Baltic region [ Baker‐Austin et al , ; Bier et al , ; Levy , ]. What is uncertain is the impact on diseases caused by marine Vibrios , in fact, the IPCC has low confidence in predicting the impact that this hypoxia has on these ecosystems, especially in the context of human health [ Barros et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s cases of reported hypoxic zones have increased dramatically with some of the more recent cases being documented in the Baltic Sea, an area undergoing rapid sea surface temperature warming [ MacKenzie and Schiedek , ; Meier et al , ]. Recently, infections caused by such pathogenic Vibrio species as V. vulnificus, V. parahaemolyticus, and V. cholerae are being reported in areas where such infections were never seen before, as far as 65°N, during unseasonably warm heat wave phenomena [ Baker‐Austin et al , ; Bier et al , ; Levy , ]. Although the aforementioned increases were not specifically investigated in the context of hypoxia, it has been shown that hypoxia is positively correlated with temperature and is at its peak during summer months worldwide [ Rabalais et al , ], corresponding to high levels of Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%